Smart door lock design and development using the pahl and beitz approach - Rizky Reynaldy Brahmana; Mochamad Tutuk Safirin (Universitas Ahmad Dahlan, 2025)
Security vulnerabilities in conventional locks and existing smart locks necessitate innovative solutions that integrate robust authentication mechanisms. This study addresses the research gap by developing a smart door lock system that uniquely combines Indonesia's government-issued e-KTP (embedded with an RFID chip) and a capacitive touch sensor for multi-factor authentication, enhancing security while ensuring universal accessibility. The design process employs the Pahl and Beitz systematic engineering methodology, emphasizing iterative optimization through planning, conceptual design, embodiment design, and detail design phases. Key specifications, including e-KTP compatibility, cost-effectiveness <IDR 1 million, and energy efficiency, were prioritized. Prototype evaluations revealed that the final design achieved superior functionality, scoring 87/100 in a multi-criteria assessment. The assessment considered components, space, aesthetics, cost, and manufacturability. The system integrates an Arduino Nano Microcontroller, a 9V battery with a 17-day lifespan, and IoT connectivity for real-time feedback. Comparative analysis demonstrates a 40–60% cost reduction compared to commercial alternatives, alongside tamper-resistant advantages from e-KTP integration system, modularity potential, and rechargeable battery. This study underscores the viability of leveraging national ID systems in IoT security frameworks, offering policymakers and manufacturers actionable insights for scalable, standardized smart home solutions.